Third Century University – a Factor Reducing Social and Cultural Exclusion of the Elderly People in the Region - Maskuliūnienė, Džiuljeta; Maskuliūnas, Bronius (Acta humanitarica academiae Saulensis, 2019)
The problems of the elderly people are becoming an increasingly relevant object of research. Third Century Universities are a modern form of non-formal adult education that is increasingly becoming more popular and recognized in Lithuania. Larger or smaller third century universities in various parts of Lithuania are gradually becoming an important form of cultural life for the elderly people, a tool for reducing social exclusion. Sociologists claim that the elderly people face a dual social exclusion: cultural – driven by negative societal attitudes, and economic – driven by poverty. This is particularly felt by people of the periphery, remote regions, as the standard of living here is lower and their cultural field provides less opportunities to meet the various needs of a 21st century person.The aim of this article is to discuss the Third Century University as a factor reducing social and cultural exclusion of the elderly people in the regions. Research methods are as follows: the analysis of theoretical literature, case analysis (the experience of the Faculty of Humanities of Šiauliai Third Age University is analysed), the analysis of semi-structured questionnaire data.The phenomenon of the Third Century University is examined in a socio-cultural context, emphasizing social exclusion, quality of life and other aspects. The article provides a brief overview of research on Third Century Universities in Lithuania. The conclusion can be drawn that Third Century Universities undoubtedly contribute to improving the quality of life of the elderly people, as subjective well-being is also linked to access to education. In addition, TCU also helps to prevent the marginalization of people of retirement age, improves social integration of retirees into society. Meeting the need for self-education also solves problems of social exclusion: without investing large sums, people of retirement age can attend quality studies, learn useful things, and communicate with their peers. In turn, Third Century Universities enrich social and cultural life of the region through their activities.
Keywords: Third Century University (TCU); humanitarian view; quality of life; social and cultural exclusion; case study